Antibacterial and Inhibitory Activity of Nora and Mepa Efflux Pumps of Estragole Complexed to β-Cyclodextrin (ES/β-CD) In Vitro Against Staphylococcus aureus Bacteria, Molecular Docking and MPO-Based Pharmacokinetics Prediction - Roger Henrique Sousa da Costa; Renata Torres Pessoa; Eduardo dos Santos Silva; Isaac Moura Araujo; Sheila Alves Gonçalves; Janaína Esmeraldo Rocha; Francisco Nascimento Pereira Junior; Naiara Cipriano Oliveira; Victor Moreira de Oliveira; Matheus Nunes da Rocha; Emmanuel Silva Marinho; Natália Kelly Gomes de Carvalho; et al. (Pharmaceutics)
Background/Objectives: The work investigates the effect of the estragole complex encapsulated in beta-cyclodextrin (ES/β-CD) in modulating bacterial resistance, specifically in Staphylococcus aureus strains expressing NorA and MepA efflux pumps. Efflux pumps are mechanisms that bacteria use to resist antibiotics by expelling them from the cell. Methodology: Several compounds and antibiotics, such as ciprofloxacin and norfloxacin, were used to evaluate the antimicrobial activity and the ability of the ES/β-CD complex to reverse resistance. Methods: The study included scanning electron microscopy assays, minimum inhibitory concentration (MIC) determination, and efflux pump inhibition tests. Results: The ES/β-CD complex did not show significant direct antibacterial activity. However, it modulated the action of norfloxacin, decreasing the MIC when combined with this antibiotic in the 1199B (NorA) strain. These results suggest a potential for synergy but not a direct inhibition of efflux pumps. Conclusion: ES/β-CD can potentiate the efficacy of some antibiotics but does not directly act as an efflux pump inhibitor; it is more of an antibiotic potentiator than a direct solution to bacterial resistance. The molecular docking simulation data suggest its high affinity for forming the ES/β-CD complex. The pharmacokinetic predictions based on MPO suggest that the compound has moderate lipophilicity, highly effective cellular permeability, and low incidence of organic toxicity, pointing to a promising pharmacological principle with controlled daily oral dosing. Conclusions: These results indicate this complex’s possible and relevant association as an adjuvant in antibiotic therapy to reduce multidrug-resistant bacteria; however, new in vivo assays are necessary to confirm this effect.